Perancangan Sistem Administrasi Keuangan Menggunakan Prototype dan Iso 25010 Pada PT Snapdev Digital Indonesia - Aji Zainuri; Ibnu Rosyid; Chairul Anwar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
In the digital era, leveraging information technology is crucial for organizations seeking to boost operational efficiency, particularly through the integration of financial systems. Within the technology industry, PT Snapdev Digital Indonesia faces several challenges, such as semi-manual transaction recording, a susceptibility to data duplication, and slow financial reporting processes. Consequently, this research aimed to design and implement a web-based Financial Administration System using the Prototyping method. The application's feasibility was comprehensively evaluated based on the ISO/IEC 25010 global software quality standard. A quantitative methodology was employed, utilizing questionnaires distributed to active system users via purposive sampling. Quality assessment focused on the eight key indicators of ISO/IEC 25010. Actual results showed the following performance levels for each characteristic: Functional Suitability 82.14% (Very Good), Performance Efficiency 76.43% (Good), Compatibility 77.14% (Good), Usability 78.21% (Good), Reliability 80.71% (Good), Security 82.14% (Very Good), Maintainability 76.43% (Good), and Portability 77.86% (Good). Based on these aggregated results, the software achieved an average score of 79.14%, indicating that the financial management system falls within the "Good" feasibility category. In conclusion, the developed system is highly suitable for implementation to enhance the effectiveness, precision, and transparency of cash management at PT Snapdev Digital Indonesia.